High endothelin-converting enzyme-1 expression independently predicts poor survival of patients with esophageal squamous cell carcinoma. Issue 9 (September 2017) - Wu, Ching-Fang; Lee, Ching-Tai; Kuo, Yao-Hung; Chen, Tzu-Haw; Chang, Chi-Yang; Chang, I-Wei; Wang, Wen-Lun
Patients with esophageal squamous cell carcinoma have poor survival and high recurrence rate, thus an effective prognostic biomarker is needed. Endothelin-converting enzyme-1 is responsible for biosynthesis of endothelin-1, which promotes growth and invasion of human cancers. The role of endothelin-converting enzyme-1 in esophageal squamous cell carcinoma is still unknown. Therefore, this study investigated the significance of endothelin-converting enzyme-1 expression in esophageal squamous cell carcinoma clinically. We enrolled patients with esophageal squamous cell carcinoma who provided pretreated tumor tissues. Tumor endothelin-converting enzyme-1 expression was evaluated by immunohistochemistry and was defined as either low or high expression. Then we evaluated whether tumor endothelin-converting enzyme-1 expression had any association with clinicopathological findings or predicted survival of patients with esophageal squamous cell carcinoma. Overall, 54 of 99 patients with esophageal squamous cell carcinoma had high tumor endothelin-converting enzyme-1 expression, which was significantly associated with lymph node metastasis ( p  = 0.04). In addition, tumor endothelin-converting enzyme-1 expression independently predicted survival of patients with esophageal squamous cell carcinoma, and the 5-year survival was poorer in patients with high tumor endothelin-converting enzyme-1 expression ( p  = 0.016). Among patients with locally advanced and potentially resectable esophageal squamous cell carcinoma (stage II and III), 5-year survival was poorer with high tumor endothelin-converting enzyme-1 expression ( p  = 0.003). High tumor endothelin-converting enzyme-1 expression also significantly predicted poorer survival of patients in this population. In patients with esophageal squamous cell carcinoma, high tumor endothelin-converting enzyme-1 expression might indicate high tumor invasive property. Therefore, tumor endothelin-converting enzyme-1 expression could be a good biomarker to identify patients with worse survival and higher risks of recurrence, who might benefit from the treatment by endothelin-converting enzyme-1 inhibitor.